Advantages of Electrochemically Synthesized Organic Compound in the Corrosion Inhibition with Azoschiffs Base - S. A. Shreekanta; R. Purushothama (Current Topics on Chemistry and Biochemistry Vol. 4, 2022)
In the present study, direct reduction in the aromatic ring by electrochemical route at the laboratory scale is explored. This concept is conceived as a preparatory attempt to accomplish an alternative course to the tedious chemical route and to invent a direct method of incorporating the Azo-imine groups into the aromatic ring moiety, in a single step. The experimental part comprises of two segments – Electro synthetic work and Electro analytical work. The electrochemically synthesized azodye shows corrosion inhibition efficiency on forming a layer of hydrophobic film on the surface of steel. The corrosion inhibition of electrochemically synthesized azo Schiff bases shows good result compare to azo schiffs bases which is synthesised by conventional method, then it was studied by weight loss method.